WEB-BASED GENIALLY MEDIA FOR UNDERSTANDING THE FOOD CHAIN MATERIAL IN ELEMENTARY SCHOOLS - Alfie Rahmi Azida; Framz Hardiansyah; Ali Armadi (Universitas Islam Negeri Mataram, 2025)
Science education in elementary schools faces challenges in teaching complex and abstract materials, such as food chains, which require deep visual and conceptual understanding. This study aims to evaluate the effectiveness of using web-based genetic media in improving students' understanding of food chain material in science learning in elementary schools. This study used a quasi-experimental design with two groups: the experimental group using web-based Genially Media and the control group using conventional learning methods. Data were obtained through pre-tests and post-tests measured by objective test instruments. The results showed that the experimental group experienced a significant increase in understanding, with an average N-gain of 0.66, while the control group only obtained an N-gain of 0.29. The t-test confirmed that the difference between the experimental and control groups was significant (p = 0.000). These findings indicate that web-based genetic media improves students' understanding of food chain material. The implications of this study provide a basis for the application of web-based technology in science learning in elementary schools and encourage the development of more interesting and effective interactive learning methods. This study also suggests further research with stronger experimental designs and larger samples.